The Application Of Analysis SWOC In The Strategic Plan Education (BIDAYAH: STUDI ILMU-ILMU KEISLAMAN, 2017)
SWOC analysis is one of step that can be taken in making an education strategical plan. This analysis is done to see deeply situation internal and external organization. The internal situation seen is a power (strengths) and organization for education (weaknesses). The situation of external (opportunities) and (challenges). To better strategical plan can be done by analyzing any strength, weakness, opportunities and challenges. Available this analysis will be deliver combination strength-opportunities strategy, power, weakness, opportunities and weakness, and challenges.